Exact Null Controllability of KdV-Burgers Equation with Memory Effect Systems - Rajagounder Ravi Kumar; Kil To Chong; Jong Ho Park (Abstract and Applied Analysis, 2012)
This paper is concerned with exact null controllability analysis of nonlinear KdV-Burgers equation with memory. The proposed approach relies upon regression tool to prove controllability property of linearized KdV-Burgers equation via Carleman estimates. The control is distributed along with subdomain ω⊂Ω and the external control acts on the key role of observability inequality with memory. This description finally showed the exact null controllability guaranteeing the stability.